2018
DOI: 10.36076/ppj.2018.4.e377
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal Root Ganglion Stimulation (DRGS) for the Treatment of Chronic Neuropathic Pain: A Single-Center Study with Long-Term Prospective Results in 62 Cases

Abstract: Background: Dorsal root ganglion stimulation (DRGS) treats discrete, localized areas of neuropathic pain. But there are no long-term results available so far. Objectives: We studied the long-term outcome of DRGS used in the treatment of chronic neuropathic pain. Study Design: A prospective, longitudinal single center investigation. Setting: Academic medical center in Germany. Methods: Patients (age >18 years) with chronic neuropathic pain in the hands, back, legs, knees and feet were prospectively examined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 25 publications
(32 reference statements)
3
61
1
9
Order By: Relevance
“…The overall incidence rate of 3.2% for DRG stimulation was comparable to the event rate for fully-implantable SCS systems (3.1%) from the same manufacturer and so represents a true comparison of rates given that the same requirements for reporting and methods for data collection were taken as a part of the required device vigilance monitoring. These rates are similar to those observed during the ACCURATE clinical trial conducted for FDA approval as well as those reported in the literature (11,12,15,17,18,30). The latter of these two data collection methods (clinical studies) yield fairly large ranges of events, mostly due to the heterogeneity in data collection methods, reporting decisions and the fact that data was obtained from different geographies as well as different clinical sites.…”
Section: Discussionsupporting
confidence: 84%
“…The overall incidence rate of 3.2% for DRG stimulation was comparable to the event rate for fully-implantable SCS systems (3.1%) from the same manufacturer and so represents a true comparison of rates given that the same requirements for reporting and methods for data collection were taken as a part of the required device vigilance monitoring. These rates are similar to those observed during the ACCURATE clinical trial conducted for FDA approval as well as those reported in the literature (11,12,15,17,18,30). The latter of these two data collection methods (clinical studies) yield fairly large ranges of events, mostly due to the heterogeneity in data collection methods, reporting decisions and the fact that data was obtained from different geographies as well as different clinical sites.…”
Section: Discussionsupporting
confidence: 84%
“…These results are comparable to other published literature. Morgalla et al reported >70% responder rate for focal (mainly groin and knee) pain at three years (28,29). Moreover, a large retrospective study of 271 patients showed similar pain reduction regardless of focal area being treated (46).…”
Section: Discussionmentioning
confidence: 96%
“…Die Dorsalganglienstimulation ist eine wichtige Neue rung, mit der es erstmals möglich ist, kleine, abgeschlos sene Schmerzareale wie beispielsweise Knie oder Leisten schmerzen gezielt zu behandeln. Obwohl diese Stimula tionsform erst seit wenigen Jahren zur Verfügung steht, gibt es hierzu eine große Anzahl von Studien und Lang zeitergebnissen [29][30][31][32][33][34]. In einer Studie mit 62 Patien ten konnte gezeigt werden, dass über einen Zeitraum von 3 Jahren eine sehr gute Schmerzlinderung von mehr als 50 % erreicht werden konnte (p < 0,0001) [30].…”
Section: Dorsalganglienstimulationunclassified
“…Obwohl diese Stimula tionsform erst seit wenigen Jahren zur Verfügung steht, gibt es hierzu eine große Anzahl von Studien und Lang zeitergebnissen [29][30][31][32][33][34]. In einer Studie mit 62 Patien ten konnte gezeigt werden, dass über einen Zeitraum von 3 Jahren eine sehr gute Schmerzlinderung von mehr als 50 % erreicht werden konnte (p < 0,0001) [30]. Darüber hinaus scheint die Dorsalganglienstimulation insbeson dere bei CRPS der herkömmlichen Stimulation überlegen zu sein [35].…”
Section: Dorsalganglienstimulationunclassified